Food-specific IgG4-guided diet elimination improves allergy symptoms in children - Yang, Boyun; Yu, Hanxiao; Yao, Wo; Diao, Ran; Li, Bohui; Wang, Yongfang; Li, Ting; Ge, Liuya; Hu, Yingying; Wang, Huiying (Frontiers in Immunology, 2024)
Allergic diseases in children are major public health concerns due to their widespread and rising prevalence. Food specific immunoglobulin G4(FS-IgG4) have been detected in patients of allergic diseases, but its clinical significance is still in argue. In present study, 407 children with allergic diseases were recruited and categorized into three groups according to the different systems involved as respiratory system group, skin system group and multiple system group with the collection of clinical symptoms and serum antibodies of total immunoglobulin E (IgE), house dust mite (HDM) IgE, food specific IgE (FS-IgE) and FS-IgG4. Part of these patients were followed up with the intervention of FS-IgG4 guided diet elimination with or without add-on probiotics supplement. The analysis at baseline revealed the distinct serum level of different antibodies. The positive rate of FS-IgG4 in all groups were more than 80%, and the proportion of total IgE and FS-IgG4 both positive in the multisystem group was the highest (p=0.039). Egg and milk were the food with the highest positive rate of FS-IgG4 in all groups. After diet elimination for more than 3 months, serum FS-IgG4 in children was significantly decreased (P＜0.05)along with the improvement of clinical symptoms, regardless the add-on of probiotics or not. However, the intervention didn't impact the serum levels of total IgE, FS-IgE and HDM IgE. There was no further decrease of serum FS-IgG4 level in children followed up for more than 1 year, which may be related to the incompliance of diet elimination. Multivariate regression analysis revealed that the decline of serum FS-IgG4 was an independent predictable factor for the improvement of clinical symptoms (adjusted OR:1.412, p=0.039). Add-on of probiotics showed less efficient in the reduce of FS-IgG4 level more patients with relief of clinical symptoms. Our results confirmed the correlation between FS-IgG4 and allergic diseases, the decreased FS-IgG4 could be a useful predictor for the improvement of allergic symptoms. FS-IgG4 guided diet elimination is an efficient treatment for allergic diseases. Our study adds solid data to the clinical significance of FS-IgG4 in allergic diseases.